How and When? Metacognition and Solution Timing Characterize an “Aha” Experience of Object Recognition in Hidden Figures - Ishikawa, Tetsuo; Toshima, Mayumi; Mogi, Ken (Frontiers in Psychology, 2019)
The metacognitive feelings of an “aha!” experience are key to comprehending human subjective experience. However, behavioral characteristics of this introspective cognition are not well known. An aha experience sometimes occurs when one gains a solution abruptly in problem solving, a subjective experience that subserves the conscious perception of an insight. We experimentally induced an aha experience in a hidden object recognition task, and analyzed whether this aha experience was associated with metacognitive judgments and behavioral features. We used an adaptation of Mooney images, i.e., morphing between a greyscale image and its binarised image in 100 steps, to investigate the phenomenology associated with insight: aha experience, confidence, suddenness, and pleasure. Here we show that insight solutions are more accurate than non-insight solutions. As metacognitive judgments, participants' confidence in the correctness of their solution is higher in insight than non-insight problem solving. Intensities of the aha feeling are positively correlated with subjective rating scores of both suddenness and pleasure, features that show marked signs of unexpected positive emotions. The strength of the aha experience is also positively correlated with response times from the onset of presentation until finding the solution, or with task difficulty only if the solution confidence is high enough. Our findings provide metacognitive and temporal conditions for an aha experience, characterizing features distinct from those supporting non-aha experience.